Pengaruh Pola Pergerakan Kendaraan Terhadap Karakteristik Arus Lalu Lintas Pada Ruas Jalan Slamet Riyadi Surakarta - Setiawan, Dedy arif, Dr. Nurul Hidayati, Ika Setiyaningsih, ST, MT (2016)
ABSTRACT THE INFLUENCE OF THE VEHICLE PATTERN TO TRAFFIC FLOW CHARACTERISTICS AT SLAMET RIYADI ROADS, SURAKARTA The differences every drivers in the roads causes some movement patterns happen. This is very closest relation with traffic flow characteristics such as volume, speed, and density. Moreover in city areas that traffic flow very dense like in Slamet Riyadi roads, Surakarta. This research aim to knows the vehicle movement pattern, to knows the traffic flow condition is see from speed and flow rate in Slamet Riyadi roads, Surakarta also to knows the influence of vehicle movement pattern to traffic flow like was mention in above. This research was conducted in Slamet Riyadi roads, Surakarta that the roads with 3 line 1 direction type and 1 line again was used on street parking. In this research the line that used is second line from south or can called right line. The data was used such as traffic video recording, roads geometric, areas condition also road network map. Taking the data was conducted on Thursday, 18 December 2014 at 09.05 - 14.05 WIB. The analysis method that was used is multy regression analysis by helping SPSS 15 version programs. The parameter was used such as the relation of vehicle movements pattern with traffic flow caharacteristics (speed and volume). Based on the result of the research, was get 19 movement patterns. Pattern I, II, III and add I only consist of car only that have different position in one line. Pattern IV - VII consist of one car and one until two motorcycle in one line. The other patterns (13 patterns) only consist of one until two motorcycle that have different position in one line. Number of events of all pattern maximal happen at 10.10 - 10.14 with 159 events, and was get Vs is 43.56 kilometres/hour, while number of events the smallest happened at 13.15 - 13.19 with 103 events, and get Vs is 45,65 kilometres/hour. The value of flow rate (Q) all of patterns that the most happened at 10.10 - 10.14 with 181 kend/5' or 1336,80 amp/hour, while the flow rate (Q) the smallest happened at 13.40 - 13.44 with 109 kend/5' or 883,20 smp/hour. Based on analysis the relation between movement patterns (P1) until Adding Patterns (PTIII) with Speed (Vs) or flow rate (Q) was get the formulas such as: Vs = 48,555 - 0,049 PI - 0,034 PII+ 0,050 PIII + 0,10 PIV - 0,311 PV - 0,452 PVI - 0,015 PVIII + 0,137 PIX - 0,094 PX - 0,030 PXI - 0,502 PXII - 0,692 PXIII - 0,239 PXIV + 0,164 PXV - 0,163 PTI - 0,097 PTII + 0,062 PTIII Q = 0,079 + 12,009 PI + 12,017 PII + 23,890 PIII + 16,866 PIV + 16,741 PV + 21,358 PVI + 4,795 PVIII + 4,783 PIX + 4,793 PX + 9,624 PXI + 9,486 PXII + 14,344 PXIII + 14,423 PXIV + 14,033 PXV + 12,016 PTI + 9,665 PTII + 9,630 PTIII From the second formulas in above have the value with 0,286, with 1,000 and was saw from each other the value of t Test also F Test then can be concluded that vehicle movement patterns with speed individually or together (Pattern I until Adding Pattern III) not influence to the speed, while the vehicle movement patterns with flow rate can be seen from other the value t Test also F Test then can be concluded that vehicle movement patterns with flow rate individually or together (Pattern I until Adding Pattern III) influence the flow rate. Key word: movement pattern, characteristics, speed, flow rate, regression